Potensi mikroba penambat nitrogen dan pelarut fosfat untuk optimalisasi pertumbuhan dan hasil tanaman kedelai - Miftah Dieni Sukmasari; Acep Atma Wijaya; Umar Dani; Sri Umyati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to evaluate the effect of nitrogen-fixing microbes and phosphate solubilizing microbes on the growth and yield of soybean. Research conducted in practicum land Faculty of Agriculture, the University of Majalengka from January to May 2019. The method used in this research was a factorial randomized block design consisting of 16 treatments repeated three times. The first factor was inoculant of nitrogen-fixing microbial (n), which consists of n0 (without inoculation), n1 (5 g inoculation MPN/kg seeds), n2 (10 g inoculation MPN/kg seeds), n3 (15 g inoculation MPN/kg seeds). The second factor was phosphate solubilize microbe (b) consists of b0 (0 kg/ha of phosphate solubilizing microbes), b1 (50 kg/ha of phosphate solubilizing microbes), b2 (100 kg/ha of phosphate solubilizing microbes), and b3 (150 kg/ha of phosphate solubilizing microbes). The differences between average were tested using Duncan's multiple range test. The analysis showed that the application of both nitrogen-fixing microbial and phosphate solubilize microbes was an effect on the growth and yield of soybean plants. N-fixing microbes and phosphate solvents effect on plant height, the number of productive branches, leaf area index, except on the number of filled pods, the number of grain per plant, weight of 100 grains, the weight of grain per plant, and weight of grain/plot, most optimal dose is 150 kg/ha MPF. The most optimal dose is 5 g for MPN inoculation and 100 kg/ha for MPF on the mean of the observed variables.